Análisis de la satisfacción de los pacientes para mejorar la atención del Hospital de Apoyo Leoncio Prado del distrito de Huamachuco, período 2012 al 2014. - Arteaga Araujo, Esther Marilina (2015)
This research aims to determine the degree of satisfaction of patients in the Hospital de ApoyoLeoncio Prado district of Huamachuco in each of the dimensions of quality in order to propose improvements to increase the goals of care in the hospital. The research question is referred to the following question: What is the degree of satisfaction of patients to improve care of Support Hospital Leoncio Prado district of Huamachuco period 2012 to 2014 ?, whose hypothesis is: The patient satisfaction will positively influence to improve the care of Support Hospital Leoncio Prado district of Huamachuco period 2012 to 2014, highlighting as variables of study: Independent Variable: Patient satisfaction; and the dependent variable: Customer service. Design was used descriptive investigation and inductive methods; analytical, statistical and technical research data collection, as the survey. In surveys of hospital patients Leoncio Prado, the level of service to patients is 22.57%, with a very low level compared to national standards, this is a very worrying indicator for the level of service is very low. In this thesis, each question in the questionnaire was analyzed and plotted graphically, these results were the basis for the formulation of strategies to improve staff recruitment. In addition to formulating conclusions and recommendations of this research.